Grand Design for Merapi Irrigation Channel System Using Watershed and River Region Approaches based on Community Development in Yogyakarta, Indonesia - Slamet Suprayogi; Totok Gunawan; Sigit Heru Murti; Wikan Jaya Prihantarto; Masrur Alatas (ASEAN Journal on Science and Technology for Development, 2022)
This paper proposes a grand design for Merapi Irrigation Channel, an irrigation channel system spanning from Turi to Cangkringan District in Yogyakarta, Indonesia. This design is based on Geographic Information System research to assess the feasibility of the system from two aspects, namely geophysics using site selection approaches (watershed and river region) and community aspirations, analyze potential water resource availability to support its sustainability, and construct a grand design. Primary data acquired from IKONOS image interpretation were used to collect geophysical and ?eld data for parameter mapping, and spatial data were modeled using Geographic Information System technology to determine paths, directions, and routes. Community aspirations were obtained by structured interviews with key informants and focus group discussions with community groups in village units. Results showed that the land carrying capacity geophysically allowed Krasak–Bedog Rivers as the permanent discharge of 123.78 m3/s of water, which is consistent with community aspirations for high irrigation water discharge in traversed districts. Overall, 19 rivers and 9 arti?cial retentions in the channel system respectively produced maximum discharges of 123.78 and 12 m3/s. The grand design included the construction of a 41 km long Merapi Channel from Turi (speci?cally Wonokerto Village) at 500 masl to Cangkringan (Glagaharjo) at 450 masl.